Finishing properties of a particleboard / Nur Ain Jemain, Nur Hannani Abdul Latif and Junaiza Ahmad Zaki - Jemain, Nur Ain; Abdul Latif, Nur Hannani; Ahmad Zaki, Junaiza (2012)
High level of demand occurred to high quality furniture in Malaysia. The quality of furniture produced is depending on the material and manufacturing process. Finishing quality of the furniture also plays their role in classifying the quality level of a product. This study is conducted to determine the effect of hardener, different particle sizes and finishing systems application on a particleboard from Gliricidia sepium. The particleboards been produced with hardener and without hardener and the particle sizes been used in these studies are 1mm and 0.5 mm. Two different finishing system applications were then applied by using acid catalyst (AC) lacquer. Different finishing testing was conducted in determining the finishing properties of the particleboard, which is physical (surface roughness, pencil hardness and tape adhesion) and mechanical (household test using vinegar, detergent and sauce) testing. From this study, it was found that there is highly significant different on the surface roughness testing when the hardener, different particle sizes and finishing system applications been applied. Pencil hardness testing showed the same pattern but there is no significant different when using different particle sizes. For tape adhesion testing, all variables showed no significant different except for different finishing system application. Meanwhile, for household test, only different particle sizes showed that there is significant different on the finishing properties of particleboard. Indirectly, this study also wants to introduce Gliricidia sepium, as an alternative material for particleboard.